Cost Calculation and Selling Price Determination for MSME in Jababeka Industrial Area - Supeni Anggraeni Mapuasari; Vita Elisa Fitriana; Chita Oktapriana (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2024)
Besides the position as an industrial center, Jababeka is also a residential and MSME center that supports the regional economy. Even though they are continuouesly growing, MSMEs still need a numeruos supports to be able to develop further, including how MSMEs can accurately calculate business costs and ultimately determine the right selling price. This training was divided into two sessions, where the first session focused on the concept of business costs, while in the second session, participants were asked to directly applied the previous concept and calculate their real business costs. The results of the questionnaire distributed to all 60 MSME participants showed that this training was able to provide an understanding of cost calculations and determining product selling prices. Therefore, it can be concluded that this training has successfully contributed to the MSME growth.